The impact of two dipping systems on endemic stability of bovine babesiosis and anaplasmosis in cattle at four communal grazing areas in Limpopo Province, South Africa - Stoltsz, Wilhelm Heinrich (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2005.